Low free triiodothyronine levels in mexican pediatric population with congenital heart disease after cardiac surgery undergoing cardiopulmonary bypass. - A Araujo Martínez; L García-Benítez; E Hernández Beltrán; F Pérez Juárez; H Diliz Nava; O Tamariz-Cruz; A Palacios Macedo-Quenot (Instituto Nacional de Pediatría, 2016)
BACKGROUND: Low free triiodothyronine level in patients undergoing heart surgery with cardiopulmonary bypass (CPB) is well described in literature, but the prevalence in pediatric Mexican population is yet unknown. OBJECTIVE: To know the prevalence of postoperative low free triiodothyronine level and the associated complications after cardiopulmonary bypass exposure in pediatric population in Mexico. MATERIAL AND METHODS: A sample of free triiodothyronine (FT3) blood was obtained in the early postoperative period of patients undergoing CPB heart surgery. Postoperative low FT3 level (PLFT3) was defined as any blood value under 2.9 pg/mL. Logistical regression models were used for analysis of independent variables, adjusted for complexity score (RACHS-1) and Aristotle Comprehensive Complexity Score. RESULTS. PLFT3 was present in 35.7% of the patients (n=109). Correlation with PLFT3 the following variables were observed: prolonged CPB time (p=0.001) prolonged aortic cross clamp (p=0.002) level of complexity of the surgery as measured by Aristotle ≥3 (p=0.001) and RACHS-1 ≥3 (p=0.021). Associated complications were: postoperative arrhythmias (p=0.008) extended intubation period (p=0.008) and higher infection rate (p=0.002).